Sensitivity Analysis for Modeling of Cr(VI) Transfer From Soil to Surface Runoff - Wu, Xiujie; Xu, Zhongyuan; Tong, Juxiu; Hu, Bill X. (Frontiers in Environmental Science, 2022)
Heavy metal contamination in soil has become a serious environmental problem in China, and chromium is one of the major threats to human health. In order to better understand the transfer pattern of heavy metal hexavalent chromium from polluted sites into surface water, the influencing factors that affect solute transfer from soil into surface runoff with linear and nonlinear adsorption equations based on a two-layer incomplete mixing model were analyzed in this study. The Quasi-Newton method was used to optimize model parameters by fitting with the experimental laboratory data of chromium (Cr(VI)) in surface runoff. The local sensitivity analysis and the Morris global sensitivity analysis approaches were used to assess the parameter importance of rainfall intensity p, incomplete mixing parameter α, the soil adsorption properties, and the initial soil water content θ0. The study results showed both optimized linear and nonlinear models were consistent with the experimental results. The results of global sensitivity indicated that rainfall intensity p was the main factor influencing Cr(VI) transport from soil into surface runoff. The α in the two-layer model was another vital parameter that influenced such transport processes. Moreover, the soil adsorption properties and the θ0 had the lowest effects on the Cr(VI) loss in runoff.